Resolving the outer ring of HD 38206 using ALMA and constraining limits on planets in the system. Issue 2 (29th October 2020) - Booth, Mark; Schulz, Michael; Krivov, Alexander V; Marino, Sebastián; Pearce, Tim D; Launhardt, Ralf
ABSTRACT: HD 38206 is an A0V star in the Columba association, hosting a debris disc first discovered by IRAS . Further observations by Spitzer and Herschel showed that the disc has two components, likely analogous to the asteroid and Kuiper belts of the Solar system. The young age of this star makes it a prime target for direct imaging planet searches. Possible planets in the system can be constrained using the debris disc. Here, we present the first ALMA observations of the system's Kuiper belt and fit them using a forward modelling MCMC approach. We detect an extended disc of dust peaking at around 180 au with a width of 140 au. The disc is close to edge on and shows tentative signs of an asymmetry best fit by an eccentricity of 0.25^+0.10_-0.09 . We use the fitted parameters to determine limits on the masses of planets interior to the cold belt. We determine that a minimum of four planets are required, each with a minimum mass of 0.64 M J, in order to clear the gap between the asteroid and Kuiper belts of the system. If we make the assumption that the outermost planet is responsible for the stirring of the disc, the location of its inner edge and the eccentricity of the disc, then we can more tightly predict its eccentricity, mass, and semimajor axis to be e_p=0.34^+0.20_-0.13, m_p=0.7^+0.5_-0.3 M_J, and a_p=76^+12_-13 au .